1988
DOI: 10.1126/science.2896386
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Epidemiological Correlates of HTLV-I Infection in U.S. Blood Donors

Abstract: on sera from 39,898 blood donors at ight blood centers in ographicll dict areas of the United States. Ten donors (0.025 percent) showed cvidelcc of HLV-I seropositivity by ezme immunoassays; this was firmed by protin immunuoblot and rioimmunoprecipitation. Seoevalce rates rantd from 0 to 0.10 percent at the locations sampled, with HLV-I antbodies found predominantly in donors from the southeasten and southwestern Unitd Stateb. Matched casc-control interviews and laboratory studics werc peroirmed on five seropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0
3

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(72 citation statements)
references
References 23 publications
5
64
0
3
Order By: Relevance
“…The pronounced reactivity to gag (p19 and p24) and env (gp45-46) in The frequency of these antibodies in CFIDS patients compared with healthy, noncontact controls suggests exposure/infection with an HTLV-like agent rare in healthy noncontact people. Some adult CFIDS patients in the study were from the southeastern United States, where HTLV-I infections are more frequent, but the reported incidence of HTLV seropositivity in blood donors there is only 0.05% (22). More important, the pediatric patients reside in rural upstate New York, where population studies have shown that the HTLV seropositivity rate approaches zero (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pronounced reactivity to gag (p19 and p24) and env (gp45-46) in The frequency of these antibodies in CFIDS patients compared with healthy, noncontact controls suggests exposure/infection with an HTLV-like agent rare in healthy noncontact people. Some adult CFIDS patients in the study were from the southeastern United States, where HTLV-I infections are more frequent, but the reported incidence of HTLV seropositivity in blood donors there is only 0.05% (22). More important, the pediatric patients reside in rural upstate New York, where population studies have shown that the HTLV seropositivity rate approaches zero (22).…”
Section: Discussionmentioning
confidence: 99%
“…Some adult CFIDS patients in the study were from the southeastern United States, where HTLV-I infections are more frequent, but the reported incidence of HTLV seropositivity in blood donors there is only 0.05% (22). More important, the pediatric patients reside in rural upstate New York, where population studies have shown that the HTLV seropositivity rate approaches zero (22).…”
Section: Discussionmentioning
confidence: 99%
“…In areas where the disease is not endemic, such as Europe and North America, HTLV-1 infection is found mainly in immigrants, their offspring and sexual contacts, sex workers, and intravenous drug users (IVDU). Among blood donors in North America and Europe, the seroprevalence is very low, ranging from 0.01 to 0.03% in the United States and Canada (80,264,399) to 0.002% in Norway (350) and 0.0056% in Greece (370).…”
Section: Viral Infections Infections Caused By Htlv-1/2mentioning
confidence: 99%
“…The incidence of HTLV-I in the USA is low but appears to be increasing, especially among populations with risk factors of multiple parenteral exposure. 3 The prevalence among volunteer blood donors is 0.018%. 3 We report a case of a patient who developed HAM following allogeneic bone marrow transplantation (BMT).…”
mentioning
confidence: 99%
“…3 The prevalence among volunteer blood donors is 0.018%. 3 We report a case of a patient who developed HAM following allogeneic bone marrow transplantation (BMT). To our knowledge, this is the first reported example of such a complication occurring after BMT.…”
mentioning
confidence: 99%